2000
DOI: 10.1038/35003583
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids control spasticity and tremor in a multiple sclerosis model

Abstract: Chronic relapsing experimental allergic encephalomyelitis (CREAE) is an autoimmune model of multiple sclerosis. Although both these diseases are typified by relapsing-remitting paralytic episodes, after CREAE induction by sensitization to myelin antigens Biozzi ABH mice also develop spasticity and tremor. These symptoms also occur during multiple sclerosis and are difficult to control. This has prompted some patients to find alternative medicines, and to perceive benefit from cannabis use. Although this benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
351
1
17

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 509 publications
(383 citation statements)
references
References 19 publications
14
351
1
17
Order By: Relevance
“…Involvement of the endocannabinoid system acting at CB 1 R in the pathogenesis of MS have been supported by several studies [87][88][89][90]. There are now several lines of evidence indicative of therapeutic potentials of cannabinoids in the control of MSrelated symptoms, including tremor, which remains difficult to manage with current medications (e.g., carbamazepine, propranolol, primidone, and gluthetimide) [12,89,91,92]. Following this premise, De Lago et al [93] have shown that the nonselective cannabinoid agonist WIN 55,212-2 ameliorated neurological disability, tremor, and spasticity in the chronic relapsing experimental autoimmune encephalomyelitis murine model of MS [92].…”
Section: Cannabinoids and Ms-related Tremormentioning
confidence: 92%
See 3 more Smart Citations
“…Involvement of the endocannabinoid system acting at CB 1 R in the pathogenesis of MS have been supported by several studies [87][88][89][90]. There are now several lines of evidence indicative of therapeutic potentials of cannabinoids in the control of MSrelated symptoms, including tremor, which remains difficult to manage with current medications (e.g., carbamazepine, propranolol, primidone, and gluthetimide) [12,89,91,92]. Following this premise, De Lago et al [93] have shown that the nonselective cannabinoid agonist WIN 55,212-2 ameliorated neurological disability, tremor, and spasticity in the chronic relapsing experimental autoimmune encephalomyelitis murine model of MS [92].…”
Section: Cannabinoids and Ms-related Tremormentioning
confidence: 92%
“…Correspondingly, this study revealed the prominent role of CB 1 R activation in the relief of tremor and spasticity, as a selective CB 1 R, but not a CB 2 R, antagonist reversed the positive effects of preadministered cannabinoids; moreover, no beneficial effects were observed by administering a selective CB 2 agonist [93,94]. An earlier study reported that cannabinoid agonists Δ 9 -THC, methanandamide, R(+)WIN 55,212-2, and JWH-133 all diminished tremor and spasticity in the experimental autoimmune encephalomyelitis model, and that aggravation of the symptoms occurred after using CB 2 R and, in particular, CB 1 R antagonists [12].…”
Section: Cannabinoids and Ms-related Tremormentioning
confidence: 95%
See 2 more Smart Citations
“…A variant of EAE and second model of MS, chronic relapsing experimental allergic encephalomyelitis (CREAE), has shown very robust sensitivity to cannabinoid agents as well. For example, Baker et al [120] have investigated the role of CB1 vs. CB2 cannabinoid receptors in cannabinoid-induced suppression of the spasticity and tremor of mice with CREAE, reporting that both CB1 and CB2 receptors may play a role-CB2 possibly through their presence on immune cells in the CNS which may be signaled to down-regulate their reactivity through cannabinoid agonism [120,121].…”
Section: Multiple Sclerosismentioning
confidence: 99%